Analisis Jejaring Pelaku Pariwisata di Kabupaten Bintan : Studi pada Event Ironman Bintan - Dewi Nurwati Dewi; Adji Suradji Muhammad; Eka Suswaini (Kodepena Indonesia, 2020)
Analysis of Tourism Actors Network in Bintan Regency. This study aims to determine the network of tourism actors in Bintan Regency through the Ironman Bintan event in 2019. The problem formulation in this study is